2016
DOI: 10.1007/s00464-016-5012-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term recurrence of bile duct stones after endoscopic papillary large balloon dilation with sphincterotomy: 4-year extended follow-up of a randomized trial

Abstract: EPLBD + EBS is associated with a low rate of long-term CBD stone recurrence. However, the risk is significantly higher in patients with a more dilated CBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
2
27
0
2
Order By: Relevance
“…Although short‐term outcomes such as early adverse events and effectiveness of stone removal were reportedly not different between EPLBD with and without EST, to date, there have been no comparative studies on the long‐term outcomes of EPLBD with and without EST. Our study results suggested that long‐term outcomes after EPLBD without EST appeared comparable to those of EPLBD with EST in the previous studies . Omission of EST prior to EPLBD might be simpler and more cost‐effective, but there are some concerns about potential risks of PEP.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Although short‐term outcomes such as early adverse events and effectiveness of stone removal were reportedly not different between EPLBD with and without EST, to date, there have been no comparative studies on the long‐term outcomes of EPLBD with and without EST. Our study results suggested that long‐term outcomes after EPLBD without EST appeared comparable to those of EPLBD with EST in the previous studies . Omission of EST prior to EPLBD might be simpler and more cost‐effective, but there are some concerns about potential risks of PEP.…”
Section: Discussionsupporting
confidence: 74%
“…The propensity score of undergoing EPLBD without EST or EPBD was calculated using a multivariable logistic regression model. Bile duct diameter and gallbladder status were previously reported as risk factors for stone recurrence after EPLBD or EPBD . Furthermore, number of stones could determine whether to carry out EPLBD or EPBD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the complication rate was 6.8% only in the form of bleeding without pancreatitis or perforation. The latter remains the most severe but rare: 7 perforations (0.40%) have been reported in the literature [25]. The presence of distal stenosis of the common bile duct appears to be an independent risk factor for perforation and could be considered as a contraindication to sphincteroplasty.…”
Section: Complication Rate Of Sphincteroplastymentioning
confidence: 99%
“…Dans notre série, le taux de complications était de 6,2 %s ous forme seulement de saignement minime des berges sans pancréatite ni perforation. Cette dernière reste la plus grave mais rare :7p erforations (0,4 %) ont été rapportésd ans la littérature (dans 31 études) [23]. La présence d'une sténose distale de la VBP semble être un facteur de risque indépendant de perforation et pourrait être considéréec omme une contre indication relatived el aS MSO [24].…”
Section: Patients Et Méthodesunclassified